2020
DOI: 10.1055/a-1205-0601
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Differences in Health Awareness and Oral Health in Pregnant Women

Abstract: Objective The aim of this study was to determine the present oral health status of pregnant women depending on selected sociodemographic differences and deduce any resulting consequences for health prevention. Methods The participantsʼ data of relevance to the study such as age, school leaving qualification, migration background, smoking habits or last dentist visit were recorded using a questionnaire. The subsequent dental check-up concentrated on open carious lesions, any initiated root canal treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Regarding the predisposing factors, a strong correlation was detected between a healthier periodontal status and higher participation in medical screening and educational attainment, corroborating previous studies 21 22 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Regarding the predisposing factors, a strong correlation was detected between a healthier periodontal status and higher participation in medical screening and educational attainment, corroborating previous studies 21 22 .…”
Section: Discussionsupporting
confidence: 90%
“…Studies regarding pregnant women showed a smaller rate of participation. Kühle et al found 64.0% of pregnant women visited the dentist during pregnancy, while in the study of Przeklasa et al 64.5% of the examined pregnant women did not take part in an oral disease prophylaxis program 18 22 . Results in our study showed 68.1% of pregnant women participating in a dental health screening.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The World Health Organization (WHO) and scientific associations of dentists, gynaecologists, and obstetricians emphasize that oral care is an integral part of health care provided during pregnancy [3]. There is scientific evidence showing a correlation between periodontal disease and the occurrence of preterm labour and the birth of children with low birth weight [4,5]. The implementation of therapeutic measures reduces this risk and prevents other pregnancy complications [3].…”
Section: Introductionmentioning
confidence: 99%
“…It manifests as an inflammatory, pain-free growth of skin or mucous membrane, or as a localized, pedunculated, pleomorphic mass. The gingiva is the most typical intraoral location (almost 75%), however, it can also affect the lips, mucosa, and tongue [8][9][10]. It primarily affects the mucosal surface of females with elevated levels of steroidal hormones.…”
Section: Introductionmentioning
confidence: 99%